Construct A Disaster Resilience Measuring Framework for Hospital Buildings - Agarwal, Bindu (International Journal of Control and Automation, 2018)
As described by the Delhi Medical School, hospital catastrophe resilience is " hospital resilience is its capacity to withstand, absorb, and react to calamities while keeping and expanding lifesaving services, and then recover or adapt to its previous form." The purpose of this article is to provide a method by which the disaster preparedness of hospitals may be evaluated as a whole. Following a comprehensive literature search and Modified-Delphi consultation, A suggested assessment approach was established to quantify hospital resilience. Emergency services and surge capacity; recovery and adaptation procedures; emergency preparedness; command, communication, and cooperation system; disaster plan; resource stockpile; staff capabilities; disaster training and exercises; hospital security; these are the eight critical areas mentioned. Using a specialized questionnaire, data were gathered from 41 tertiary hospitals in India Shandong Province for this research. The framework's fundamental structure was determined using factor analysis.